The Role of Entrepreneurial Vigilance Antecedents on Entrepreneurial Vigilance in A Crisis Situation: Conceptual View - Yosri Addassi; Sinda Ben Sedrine Doghri (Communications of International Proceedings, 2024)
The Covid-19 crisis is a historic event which has brought attention to a vital concept: vigilance. Entrepreneurial alertness is a concept that has the potential to contribute significantly to our understanding of how new ideas are initiated and pursued. In this article, we will examine the role of vigilance during a crisis and explore the factors influencing vigilance in such situations.
Keywords: entrepreneurial vigilance; experience; leadership style